Agro-Techono Urban Farming Development Model to Strenghten Integrated Agriculture and Tourism - Narita Amni Rosadi (Journal of Biology, Environment, and Edu-Tourism, 2025)
Agro-Techono Urban Farming is a rapidly growing technological innovation in agriculture, offering effective solutions to the challenges faced by the agricultural sector amid urbanization and population growth. This study aims to explore the implementation of Agro-Techono Urban Farming in various cities worldwide, focusing on its benefits, challenges, and impacts. The research method used is a literature review, involving an analysis of academic sources and case studies from regions that have adopted smart farming technologies such as the Internet of Things (IoT), drones, soil sensors, and data-driven agricultural management systems. The findings indicate that these technologies improve productivity, enhance water and fertilizer use efficiency, reduce operational costs, and strengthen urban food security. For instance, soil sensors enable real-time monitoring of moisture levels, allowing more efficient irrigation, while drones facilitate early detection of pests and plant diseases. However, the adoption of these technologies faces several challenges, including limited access, lack of training, regulatory constraints, and high initial investment costs. In conclusion, the successful implementation of Agro-Techono Urban Farming requires strong support from both government and the private sector through training programs, resources, and incentives for farmers.